Transfer of Roles and Bureaucratic Administrative Structures from Central to Local Government in the Kingdom of Cambodia - Norkaew, Yutthasart; MEN, Sokheang (Journal of Political and Social Agenda, 2023)
This article aims to 1) study the process of transferring roles and bureaucratic structures from central government to local governments, and 2) find policy guidelines for solving problems in transferring roles and bureaucratic structures from central government to local governments in the Kingdom of Cambodia. The study is found that 1) decentralization from central government to local government in the Kingdom of Cambodia, it is a decentralization of fiscal, administration and political power to local agencies. However, local governments are unable to decide on certain tasks by themselves or some tasks can decide by themselves and can only decide on certain matters at certain times, 2) the transfer of roles and responsibilities from the central government to municipalities, districts and sub-districts, consisting of 204 municipalities, districts, provinces (Khans) and 1,652 sub-district municipalities (Sangkats). Yet local governments are gradual, not the demolition of the existing bureaucratic structures. But focusing on the transfer of various agencies into an integrated integration, and 3) "National Committee for Sub-National Democratic Development" (NCDD) is an agency that receives important missions directly from government to decentralize the Ministry and 18 different institutions to carry out the transfer of the most efficient roles and bureaucratic structures to the local government permanently in the future.